Association between dietary knowledge and muscle mass in Chinese older adults: a cross-sectional and longitudinal study - Qiaoling Liu; Luonan Wang; Yuge Ma; Yunjie Geng (BMJ Open, 2023)
Objectives This study aims to explore the possible association between dietary knowledge and muscle mass in a Chinese population aged 60 years and above.Design Cross-sectional and longitudinal studies.Setting Data from the 2006 and 2011 China Health and Nutrition Survey (CHNS) were used for this study.Participants A total of 1487 Chinese participants (44.38% males) aged 60 and above in the 2006 survey were included in the cross-sectional study. From the same study population, a total of 1023 participants (46.82% males) with normal muscle mass on the interview date of 2006 were included in the longitudinal study.Outcome measures Dietary knowledge was accessed by a validated CHNS questionnaire. Appendicular skeletal muscle mass was calculated using a validated anthropometric equation derived from a representative Chinese population. Based on the 2021 Chinese consensus on sarcopenia, the appendicular skeletal muscle mass was categorised as ‘normal’ or ‘low’ using sex-specific cut-off values.Results The prevalence of low muscle mass in the study population was 31.20%, with a higher prevalence in females (34.22%). People with low muscle mass have a significantly lower dietary knowledge score (mean difference: −1.74, 95% CI −2.20 to −1.29). In the cross-sectional analysis, one score higher in dietary knowledge score was associated with a 4% lower odds of low muscle mass (OR=0.96, 95% CI 0.93 to 0.99). Compared with people in the lowest quartile of dietary knowledge, people in the highest quartile have a 44% lower odds of low muscle mass (OR=0.56, 95% CI 0.35 to 0.91). In the longitudinal analysis, no significant association was found between dietary knowledge and low muscle mass, yet the upper 95% CI was close to one (HR=0.97, 95% CI 0.93 to 1.01).Conclusions Sufficient dietary knowledge may play a protective role in maintaining normal muscle mass in Chinese adults aged 60 or above.